2003
DOI: 10.1016/s1534-5807(03)00121-7
|View full text |Cite
|
Sign up to set email alerts
|

The COP9 Signalosome Promotes Degradation of Cyclin E during Early Drosophila Oogenesis

Abstract: The COP9 signalosome (CSN) is an eight-subunit complex that regulates multiple signaling and cell cycle pathways. Here we link the CSN to the degradation of Cyclin E, which promotes the G1-S transition in the cell cycle and then is rapidly degraded by the ubiquitin-proteasome pathway. Using CSN4 and CSN5/Jab1 mutants, we show that the CSN acts during Drosophila oogenesis to remove Nedd8 from Cullin1, a subunit of the SCF ubiquitin ligase. Overexpression of Cyclin E causes similar defects as mutations in CSN or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 43 publications
2
111
0
1
Order By: Relevance
“…In the adult hermaphrodite, CYE-1 levels and activity are high throughout proliferative zone cells, falling as they enter meiotic prophase. In Drosophila, cyclin E levels also fall as germ cells enter meiotic prophase, in large part due to SCF-mediated protein degradation (Doronkin et al, 2003;Narbonne-Reveau and Lilly, 2009). However, the precipitous decrease in cyclin E levels as cells enter meiotic prophase, in C. elegans and Drosophila, is presumably not the trigger for entry into meiosis because it occurs after meiotic S phase.…”
Section: Research Articlementioning
confidence: 99%
“…In the adult hermaphrodite, CYE-1 levels and activity are high throughout proliferative zone cells, falling as they enter meiotic prophase. In Drosophila, cyclin E levels also fall as germ cells enter meiotic prophase, in large part due to SCF-mediated protein degradation (Doronkin et al, 2003;Narbonne-Reveau and Lilly, 2009). However, the precipitous decrease in cyclin E levels as cells enter meiotic prophase, in C. elegans and Drosophila, is presumably not the trigger for entry into meiosis because it occurs after meiotic S phase.…”
Section: Research Articlementioning
confidence: 99%
“…In Arabidopsis, it was observed that a defect in the Nedd8 conjugation increased the level of unmodified CUL1 (Dharmasiri et al, 2003). However, in Drosophila, neddylated CUL1 was accumulated at high levels in CSN5/Jab1 mutants (Doronkin et al, 2003). Clearly, neddylation-deficient mutants will be useful in addressing whether Nedd8 modification has a role in the turn over of cullin proteins.…”
Section: Influence Of Neddylation In Cullin Subcellular Localization mentioning
confidence: 99%
“…In support of this notion, recent studies using highly purified components showed that the CSN cleaved Nedd8 from hCUL1 catalytically . Additionally, in several organisms analysed (C. elegans, Drosophila and Arabidopsis), CSN activity is indispensable for deconjugation of Nedd8 from a number of tested cullins that include CUL1, CUL2 and CUL3 (Schwechheimer et al, 2001;Zhou et al, 2001;Yang et al, 2002;Doronkin et al, 2003;Pintard et al, 2003a). Surprisingly, requirement of the CSN for the deneddylation of spCUL4/Pcu4 might be different.…”
Section: Role Of Nedd8 Proteasesmentioning
confidence: 99%
See 2 more Smart Citations